A REVIEW OF WETLANDS AND COASTAL RESOURCES OF THE NIGER DELTA: POTENTIALS, CHALLENGES AND PROSPECTS - Nwankwoal, H. O. (Zibeline International, 2021)
Wetlands are areas where water covers the soil or is present either at or near the surface of the soil all year or for varying periods of time during the year, including during the growing season. The Niger Delta in Nigeria is the largest wetland in Africa and the third largest mangrove forest in the world with three sites listed as Ramsar Wetlands of International Importance. The Niger Delta wetlands and coastal resources are of high monetary significance to the local dwellers and the nation in general. This highly coveted wetland is changing rapidly, raising concern for its attendant implication on the communities relying upon its ecosystem potentials. A comprehensive data of the facilities delivered by wetlands is a significant key for real-time wetland ecosystem management. Existing literatures, were synthesized for this review on the potentials, challenges and prospects of the Niger Delta wetlands. It is pertinent from this review that the Niger Delta Wetland is wealthy in aquatic and terrestrial biodiversity of high financial significance to development of Nigeria, and is being challenged by natural and human activities such as dam construction, logging/lumbering, over-grazing, unrestrained tilling of soil for crop production, wetland reclamation, dredging, oil and gas exploration, over-fishing, invasive plant infestation, pollution, Coastal Infrastructure construction, poverty, droughts, desertification, sand storm, alien invasion, sea rising, erosion, etc. The Niger Delta Wetlands harbor tremendous wealth and supply many services that are necessary for human well-being such as location for spiritual renewal and recreation (eco-tourism), flood control, climate regulation, crop pollination, soil regeneration, raw material, energy, air and water purification; food chain supply, and medicines (Herbal solutions). This review postulates that in view of the immense significance and status of the Niger Delta Wetlands, effective and sequential monitoring be put in place by the establishment of centers of excellence in all universities in the Niger Delta Region with emphasis on studying the rich economic diversity of the wetland using remote sensing and Geographic Information System technologies for efficient conservation and management of the wetland resources.